Auditoria de Gestión a la Escuela de Educación General Básica “José Ingenieros”, de la ciudad de Loja, periodo 2021 - Jarro Guamán, Yessica Fernanda (2024)
The present work of curricular integration entitled audit of management to the school of basic general education "Jose Ingenieros" of the city of Loja, period 2021 was carried out with the fundamental purpose of evaluating the control system implemented by the educational institution to determine its degree of solidity and administrative efficiency, apply management indicators to determine the degree of efficiency, effectiveness and economy with which they have been executed, Submit the audit report in order to make the necessary corrections. The methodological process followed is in accordance with the provisions of the audit manual of the comptroller general of the state, being developed in its five phases: Planning where an audit program is developed detailing the activities to be followed throughout the process; Implementation all the activities described in the audit programme were carried out in which objectives and procedures were applied; Communication of results is the report which contains the respective conclusions and recommendations; Follow-up where a schedule of activities is planned for the director to consider the recommendations and thus comply with what has been established. Later conclusions were raised among the most relevant consists that the institution does not have the institutional educational project and does not have the operational plan of the institution.